Development of an Instrument for Measuring the Educational Effectiveness of the Open-Major (Autonomous Major Selection) System Using the Delphi Method: A Case Study of National University A - Lee, Yunso; Kim, Eunye (The Korean Association of General Education, 2025)
This study developed a longitudinal instrument to measure the educational effectiveness of the Open-Major (Autonomous Major Selection) System introduced at National University A in 2025. Drawing on a review of prior studies and institutional cases, we identified core domains and conducted three Delphi rounds with twelve higher-education experts to establish content validity. The finalized instrument comprises 66 items for entrants to the Division of Open Majors and 37 items for department-admitted students, structured under the Context-Input-Process-Product (CIPP) framework and administered at three time points (entry, end of the first semester, end of the first year). Designed from a student-experience perspective, the tool enables longitudinal assessment and tracking of major exploration, participation in general education and co-curricular programs, faculty-student interaction, sense of belonging, educational satisfaction, and academic achievement. The instrument provides actionable evidence for institutional performance management and curriculum quality assurance, the design of tailored first-year support policies, and the alignment and improvement of general education with exploratory courses.